ASSESMENT OF CROWN PREPARATIONS WITH "prepCheck" - A PILOT STUDY - Nothaft Maximilian; Marius Müller; Groth Eva; Rominu Mihai; Junker Rüdiger (Romanian Dental Association for Education, 2024)
Objectives The aim of the study was to find out to what extent subjective influences on the evaluation of crown preparations can be reduced by using "prepCheck" analysis software. Material and methods In the 3rd semester as part of the Curriculum Cerec, model tooth 36 was to be minimally invasively prepared in the phantom head to accommodate a fully anatomical, monolithically milled crown made of IPS e.max CAD (Ivoclar Vivadent AG, Schaan, Principality of Lichtenstein) material. In total 18 preparations were evaluated three times (two individual evaluations and one group evaluation) at intervals of three weeks. The model teeth were evaluated in two ways: (1) conventionally, visually and (2) using "prepCheck" analysis software. Cohen's Kappa coefficient and Fleiss' Kappa coefficient were used to compare the agreement between the assessments. Results Without the use of the analysis software, the overall results differed significantly. In the first assessment there was a strong agreement ( = 0.7) and in the second assessment after three weeks an adequate agreement ( = 0.4). While in all assessments with "prepCheck" a (nearly) perfect agreement was achieved ( = 1). Conclusion Using the "prepCheck" analysis software, compared to visual assessment, increases the failure rate while reducing intra- and inter-individual variability. PrepCheck is therefore a reliable instrument for evaluating preparations of model teeth, as it eliminates the human factor. At the same time, the software evaluates the preparations much more critically, which leads to higher failure rates. This can lead to demoralisation of the students. The sole use of the software for exam evaluation should therefore be critically examined; prepCheck is excellently suited as a self-assessment tool during practice times in the phantom.